2010
DOI: 10.1007/s00362-010-0349-y
|View full text |Cite
|
Sign up to set email alerts
|

A new Liu-type estimator in linear regression model

Abstract: In this paper, we introduce a new Liu-type estimator called modified Liu estimator based on prior information for the vector of parameters in a linear regression model and discuss its properties. Furthermore, we obtain that our new estimator is superior, in the mean square error matrix sense, to the least squares estimator, Liu estimator, ridge estimator and modified ridge estimator. Finally, a numerical example and a Monte Carlo simulation are done to illustrate some of the theoretical results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 12 publications
0
31
0
Order By: Relevance
“…The parameter values were chosen such that β ′ β=1, which is a common restriction in simulation studies of this type. 3,4,14 Sample sizes 50 and 100 were used. Three different values of σ (1, 5, and 10) were used.…”
Section: Monte Carlo Simulationmentioning
confidence: 99%
“…The parameter values were chosen such that β ′ β=1, which is a common restriction in simulation studies of this type. 3,4,14 Sample sizes 50 and 100 were used. Three different values of σ (1, 5, and 10) were used.…”
Section: Monte Carlo Simulationmentioning
confidence: 99%
“…The i − th element of matrix B in (4.21) is ridge and modified ridge estimators, respectively, in Liu and Yang [11]. In this section, we show that Almon-Liu estimator is better than Almon-modified Liu estimator according to the MSE criterion.…”
Section: 2mentioning
confidence: 84%
“…In this study, we have compared theoretical performances of Almon-ridge ( γ k ), Liu and Yang [11] showed with the increasing of the levels of multicollinearity, the smse values of ridge, Liu, modified ridge and modified Liu estimators are decreasing in general for the linear regression model. Moreover, they showed that the smse values of these estimators outperformed to the OLS estimator for all cases.…”
Section: Discussionmentioning
confidence: 99%
“…Our sampling experiment consists of different combinations of k; d and n. In this study, the explanatory variables are generated by the following equation [12,13]:…”
Section: Numerical Examplementioning
confidence: 99%